Assessment of Students' English Oral Proficiency Based on Degree Programme Implications for Admission Examinations - Betonio, Helen R. (2016)
Set in a Philippine state university, this study sought to investigate if there is a significant difference between college students' English oral proficiency when they are grouped according to their current degree programs. The sample was drawn from 147 sophomore college students who belong in one of the eight (8) degree programs. These students have taken a Speech Communication class during the previous semester. Using an oral proficiency test patterned from and a modified form of the Texas Oral Proficiency Test (TOPT), the students' English oral proficiency was assessed in terms of function, content, vocabulary, grammar, comprehensibility and fluency. A one-way ANOVA test of Equality of means in oral proficiency was used to analyze the data. This was followed by Post Hoc Analysis of each aspect of oral proficiency in relation to each degree program. Results show that there is a highly significant difference in the oral proficiency level of students in all areas, given by the significance value of 0.000 with 5% level of significance. Research results serve as basis for recommendations geared towards revisiting the language usage (LU) requirement set by the university in each degree program.
Keywords: English language -- Study examinations, questions, etc; English language proficiency; Admission test score